2014
DOI: 10.1177/1541204014538067
|View full text |Cite
|
Sign up to set email alerts
|

Staying Away From School

Abstract: Perceptions of school safety, fear of crime among students, and school avoidance have received increasing research attention in recent decades. Feeling unsafe at school impacts mental health, absenteeism, and academic success. We focus on a behavioral indicator of heightened concern about safety among high school students. Using 2011 National Youth Risk Behavior Survey data, we examine how crime victimization, bullying, drug use, weapon carrying, defensibility, media exposure, social integration, and school di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 46 publications
3
10
0
1
Order By: Relevance
“…Moderating effects on fear of victimization Gender and classroom hierarchy moderated the link between victimization and fear of victimization. The documented positive link between victimization and fear of victimization (Boulton et al, 2008;Hughes et al, 2015;Turner et al, 2015) was confirmed by the present study, thereby underscoring the importance of devoting research attention to this understudied issue. Our finding that girls reported more fear of victimization complies with the previously documented gender difference (Boulton et al, 2008).…”
Section: Moderating Effects On Peer Rejectionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moderating effects on fear of victimization Gender and classroom hierarchy moderated the link between victimization and fear of victimization. The documented positive link between victimization and fear of victimization (Boulton et al, 2008;Hughes et al, 2015;Turner et al, 2015) was confirmed by the present study, thereby underscoring the importance of devoting research attention to this understudied issue. Our finding that girls reported more fear of victimization complies with the previously documented gender difference (Boulton et al, 2008).…”
Section: Moderating Effects On Peer Rejectionsupporting
confidence: 82%
“…The association between victimization and fear of victimization has been confirmed by several studies (e.g., Hughes, Gaines, & Pryor, 2015;Turner, Finkelhor, Shattuck, Hamby, & Mitchell, 2015), but little is known about the moderators of this association. Boulton et al (2008) point out that research should devote more attention to the fear of victimization, because the portion of students suffering from this is non-negligible (Boulton et al, 2008).…”
Section: Victimization and Fear Of Victimizationmentioning
confidence: 90%
“…As evidenced by research (Boney-McCoy & Finkelhor, 1995;Chang et al, 2003;Hughes et al, 2015;Medina & Rodrigues, 2019;Shaffer & Ruback, 2002;Sharkey et al, 2012), there has been a historical focus on understanding the relationship between victimization, maltreatment, and child abuse with maladaptive behavior. With this background in mind, victimization in our study was examined in three areas: home, school, and neighborhood, and included a focus on a range of behaviors by the perpetrator that encompassed treating others cruelly and unfairly (see specific questions under "Measures" in the Method section below) and considered both direct and indirect impact.…”
Section: Victimizationmentioning
confidence: 99%
“…Despite this plurality of inquiries, we could not find any empirical evidence regarding the impact of victimization on PL. Since direct and indirect victimization at home, at school, and in the community can negatively affect preadolescents (Hamby et al, 2011;Hughes et al, 2015;Johnson et al, 2002), both direct and indirect victimization are represented in this inquiry.…”
mentioning
confidence: 99%
“…Feeling safe is important for a student to have a positive learning environment in school. Feeling of unsafe in school impacts mental health, absenteeism and academic success among the bullied (Hughes, Gaines, & Pryor, 2014). Schools encounter vulnerabilities to their safety and security in four major areas; 1) the design, supervision and use of school space (Astor, Meyer, & Behre, 1999;Durán-Narucki, 2008;Grana, et al, 2010;J Waller 2013;Kumar, M. O' Malley, & D. Johnston, 2008;Wilcox, et al, 2006), 2) the administrative operations and practices of the school (Vidourek, King, & Merianos, 2016) 3) the neighbourhoods and surrounding communities served by the school (Bowes, et al, 2009;Lee & Ha, 2015) and 4) the behavioural characteristics and histories of the students who are enrolled in the school (Atlas & Pepler, 1998;Farrington & Ttofi, 2011;Mohamad Salleh & Zainal, 2014).…”
Section: Delinquency and Physical Environment In Schoolmentioning
confidence: 99%